2014
DOI: 10.4172/2155-9597.1000215
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Grouping of Dominant Fecal Escherichia coli Isolates from Healthy Males and Females in Al-Kut/Wasit Province/Iraq

Abstract: Fecal isolates of Escherichia coli are divided into four main phylogenetic groups designated A, B1, B2 and D. Most commensal strains belong to group A and have fewer virulence factors than the extra intestinal pathogenic E. coli strains (ExPEC). This study was mainly designed for phylogenetic grouping of commensal fecal E. coli isolates from healthy males and females in Al-Kut City/Wasit Province/Iraq using PCR-based protocols. Also ExPEC's virulence genes were detected among these isolates. Among this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
(42 reference statements)
3
4
1
Order By: Relevance
“…The changes in the phylogenetic structure of the E. coli isolates from Europe during the period of 20 years may be the result of the increasing of food processing and change in dietary habits [ 1 , 25 ]. The results of the present study with the dominance of phylogroup B2 among E. coli isolates from adults are consistent with the previous reports presenting the second pattern of phylogenetic structure, whereas the predominance of isolates of phylogroup A among young children is in accordance with the first pattern [ 1 , 25 , 26 , 49 ]. The diet of young children aged 0.5–3 years is rather simple and in the most part consists of organic, less processed food as compared to adult diet.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The changes in the phylogenetic structure of the E. coli isolates from Europe during the period of 20 years may be the result of the increasing of food processing and change in dietary habits [ 1 , 25 ]. The results of the present study with the dominance of phylogroup B2 among E. coli isolates from adults are consistent with the previous reports presenting the second pattern of phylogenetic structure, whereas the predominance of isolates of phylogroup A among young children is in accordance with the first pattern [ 1 , 25 , 26 , 49 ]. The diet of young children aged 0.5–3 years is rather simple and in the most part consists of organic, less processed food as compared to adult diet.…”
Section: Discussionsupporting
confidence: 93%
“…E. coli assigned to phylogroup B2 dominated among adults, whereas phylogenetic group A isolates prevailed among young children. The distribution of the phylogroups among the human population represents two patterns, the first with predominance of group A typical for European population (in 1980s), Africa, South America and Asia [ 1 , 25 , 26 , 49 ], and the second pattern that the isolates of group B2 prevailed is characteristic for Europe in the 2000s, North America, Japan and Australia [ 1 , 25 ]. The changes in the phylogenetic structure of the E. coli isolates from Europe during the period of 20 years may be the result of the increasing of food processing and change in dietary habits [ 1 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, phylogenetic analysis predominantly clustered E. coli clinical isolates into B2 followed by A, B1 and D and this corroborates with ndings from previous studies [67][68][69]. However, contradicting results have been reported worldwide where A is the most abundantly isolated phylogroup [70][71][72][73]. Distribution of E. coli phylogroups among different ecological zones is in uenced by environment factor; thus, this accounts for variability in prevalence of the phylogenetic groups in different countries [74].…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of distributes indicates inter-region transmission of UPEC, DEC and commensals. It was observed that phylogenetic group A, B2 and D strains were majorly isolated from urine and this is in a rmative with all studies that conducted phylogenetic analysis of E. coli clinical isolates [67,[75][76][77] whereas B1 strains were predominantly isolated from anal/fecal swabs, this does not corroborate with previous studies which found phylogroup A strains as the most dominant fecal isolates [72,73,78].…”
Section: Discussioncontrasting
confidence: 68%